Authorities Of The National Land Agency In Settling Land Cases As A Form Of Legal Protection For Land Right Holders Whose Transfer Is Canceled (Study of Supreme Court Decision Number: 3542 K/Pdt/2021) - DHARSANA, I Made Pria; BUDIARTA, I Putu Nyoman; WAHYUNINGSIH, Dewa Ayu Trisna (Indonesia Strategic Sustainability, 2023)
Disputes over the transfer of ownership rights to land through the sale and purchase of land that often occur in society are caused by the Indonesian land registration system, which adheres to a hostile system. Certificates of land rights that have been registered have many possibilities for legal defects to arise, and the consequences will cause problems that lead to requests for Cancellation. The problems of this research are, first, what is the authority of the Office of the National Land Agency in resolving land cases, and second, what is the form of legal protection for holders of land rights whose transfers are canceled. This research is a normative law-type research using a statutory and case approach. This study concludes that first, the authority of the National Land Agency Office in settlement of land cases has been regulated in Ministerial Regulation IATR/BPN No. 21I of 2020; IBPN has two alternative land dispute settlements, namely, the first is settlement through the judiciary to obtain a court decision. Second, dispute settlement through mediation seeks a win-win solution, and a peace agreement is drawn up. The second type of legal protection for holders of land rights whose transfer has been canceled, particularly for third parties as holders of ownership rights, can be given to parties whose certificates of ownership are repressively canceled. The aim is to achieve legal clarity, providing legal protection to all parties.